2010
DOI: 10.1603/me09248
|View full text |Cite
|
Sign up to set email alerts
|

Phlebotomine Sand Flies (Diptera: Psychodidae) and Leishmania Infection in Gafanhoto Park, Divinópolis, Brazil

Abstract: The potential of Gafanhoto Park as an American cutaneous leishmaniasis (ACL) focus was evaluated by examination of sand ßy vectors of the Leishmania parasite. This forest remnant is located in a periurban area of Divinó polis, Brazil, where autochthonous cases of ACL have been reported. Sand ßy populations were monitored over a 2-yr period (2006 Ð2008) by using light traps (HP and Shannon). During systematic collections with HP traps, 824 specimens in total (342 males and 482 females) of 21 species were captur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 47 publications
2
41
0
7
Order By: Relevance
“…Brumptomyia brumpti (Larrouse, 1920), Psathyromyia campograndensis (Oliveira, Andrade Filho, Falcão & Brazil, 2001), Sciopemyia sordellii (Shan-Fauna of phlebotomine sand flies in areas with endemic American cutaneous leishmaniasis non & Del Pont, 1927), all with 6.0%, and Psathyromyia punctigeniculata, with 4.8%, presented distinct frequencies from the other species, which together accounted for 10.9% of the species captured (Table III). Evandromyia lenti was found naturally infected with Leishmania braziliensis in Minas Gerais (Margonari et al 2010), andSherlock (1996) suggests that this species may be involved in the transmission of canine visceral leishmaniasis in the State of Bahia.…”
Section: Resultsmentioning
confidence: 99%
“…Brumptomyia brumpti (Larrouse, 1920), Psathyromyia campograndensis (Oliveira, Andrade Filho, Falcão & Brazil, 2001), Sciopemyia sordellii (Shan-Fauna of phlebotomine sand flies in areas with endemic American cutaneous leishmaniasis non & Del Pont, 1927), all with 6.0%, and Psathyromyia punctigeniculata, with 4.8%, presented distinct frequencies from the other species, which together accounted for 10.9% of the species captured (Table III). Evandromyia lenti was found naturally infected with Leishmania braziliensis in Minas Gerais (Margonari et al 2010), andSherlock (1996) suggests that this species may be involved in the transmission of canine visceral leishmaniasis in the State of Bahia.…”
Section: Resultsmentioning
confidence: 99%
“…Pi. fischeri naturally infected with Leishmania braziliensis has only recently been found in the Southeast Region of Brazil (Margonari et al 2010, Rocha et al 2010, but the other species have all been found naturally infected by Leishmania (Viannia) sp. in PR and in other areas of South America (de Queiroz et al 1994, da Silva & Grunewald 1999, Luz et al 2000, Pita-Pereira et al 2005, 2009 residence of an American cutaneous leishmaniasis (ACL) case; 2.1: tree close to the veranda of home; 2.2: peridomicile, avocado tree used as a perch for birds; 2.3: peridomicile, tree close to pigsty; 3: residence of an ACL case; 3.1: peridomicile in a jaboticaba tree close to the home; 3.2: orange tree close to the pigsty and residence; 3.3: bamboo, distant 10 m from the residence, next to a pasture, a pound and a small forest; 4.1: pigsty close to the residence; 4.2: pigsty situated at the forest edge, 50 m far from the residence; 4.3: forest edge tree (50 m far the point 4.2); F: female; M: male.…”
Section: Discussionmentioning
confidence: 99%
“…intermedia suggest that it also is associated with Leishmania transmission in this region. Both species have been found to be naturally infected with Leishmania and are associated with ATL foci (Forattini et al 1972, Rangel et al 1984, Casanova et al 1995, Córdoba-Lanus et al 2006, Marcondes et al 2009, Saraiva et al 2009, Pita-Pereira et al 2009, Margonari et al 2010, Oliveira et al 2011, thereby demonstrating the great epidemiological importance of these species. Lutz and Neiva (1912) have reported that Ny.…”
Section: Discussionmentioning
confidence: 99%